Characterization of changes in total body composition for patients with head and neck cancer undergoing chemoradiotherapy using dual‐energy x‐ray absorptiometry. Issue 9 (21st November 2013) - Jackson, William; Alexander, Neil; Schipper, Matthew; Fig, Lorraine; Feng, Felix; Jolly, Shruti
Abstract Background Patients with head and neck cancer experience significant weight loss secondary to concurrent chemoradiotherapy (CCRT). Using dual‐energy X‐ray absorptiometry (DEXA) scans, we characterize total body composition changes during and after CCRT in order to develop novel clinical care models that will improve the patient's quality of life (QOL). Methods Sixty DEXA scans were obtained from 12 patients undergoing CCRT for locally advanced squamous cell head and neck cancer. DEXAs were performed at baseline, during treatment, completion of CCRT, and then 1 and 2 months posttreatment. Results Mean weight loss by treatment end was 9.5 kg (10.2%; p = .0002). On average, lean body mass (LBM) decreased 10.2% (p = .001), and fat body mass (FBM) decreased 11.1% (p = .001) during CCRT. LBM began to normalize after completion of treatment, whereas FBM continued to decline. Conclusion Substantial loss of muscle and FBM occurs in patients undergoing CCRT for head and neck cancer. To prevent long‐term disability and QOL decline after curative CCRT, clinical care interventions incorporating aggressive nutrition/exercise counseling are needed. © 2013 Wiley Periodicals, Inc. Head Neck 36: 1356–1362, 2014